CONTRIBUTION OF STATE-OWNED ENTERPRISES TO NATIONAL ECONOMIC DEVELOPMENT: A LITERATURE REVIEW STUDY ON SYNERGY, REGULATION AND STRATEGIC ROLE AMID GLOBAL COMPETITION - Agustinus Nugroho Jati; Gunawan Widjaja; Dyah Ersita Yustanti (Adisam Publisher, 2025)
This study examines the contribution of State-Owned Enterprises (SOEs) to Indonesia's national economic development, focusing on synergies between stakeholders, regulations, and the strategic role of SOEs in facing increasingly fierce global competition. Through a literature review approach, the study analyses relevant literature, policy documents, and regulations to understand how SOEs function as agents of development as well as competitive business actors. The results of the study confirm that synergy between SOEs, the private sector, and the government is essential in strengthening inclusive and sustainable economic development. In addition, regulatory reforms that improve the governance and administration of SOEs are key to increasing international competitiveness without neglecting their social function. In conclusion, with adaptive regulatory support and solid synergy, SOEs can continue to be a reliable engine of national development while effectively facing global challenges.